The Effect of Propofol and Dexmedetomidine Sedation on Norepinephrine Requirements in Septic Shock Patients: A Crossover Trial. Issue 2 (February 2019) - Morelli, Andrea; Sanfilippo, Filippo; Arnemann, Philip; Hessler, Michael; Kampmeier, Tim G.; D'Egidio, Annalia; Orecchioni, Alessandra; Santonocito, Cristina; Frati, Giacomo; Greco, Ernesto; Westphal, Martin; Rehberg, Sebastian W.; et al.
Abstract : Objectives: Propofol-based sedation may increase hemodynamic instability by decreasing vascular tone and venous return. Incremental exogenous catecholamines doses may be required to counteract such effects, aggravating the deleterious effects of sympathetic overstimulation. α-2 adrenergic agonists have been reported to decrease norepinephrine requirements in experimental septic shock. The aim of the present study is to test the hypothesis that switching from sedation with propofol to the α-2 agonist dexmedetomidine may decrease norepinephrine doses in septic shock. Design: Prospective open-label crossover study. Settings: University hospital, ICU. Patients: Thirty-eight septic shock patients requiring norepinephrine to maintain adequate mean arterial pressure and needing deep sedation with propofol and remifentanil to maintain a Richmond Agitation-Sedation Scale score between –3 and –4. Interventions: An initial set of measurements including hemodynamics, norepinephrine doses, and depth of sedation were obtained during sedation with propofol. Propofol was then replaced by dexmedetomidine and a second set of data was obtained after 4 hours of dexmedetomidine infusion. Sedation was switched back to propofol, and a final set of measurements was obtained after 8 hours. A Richmond Agitation-Sedation Scale score between –3 and –4 was maintained during the study period. Measurements and Main Results: Norepinephrine requirements decreased from 0.69 ± 0.72 μg/kg/min before dexmedetomidine to 0.30 ± 0.25 μg/kg/min 4 hours after dexmedetomidine infusion, increasing again to 0.42 ± 0.36 μg/kg/min while on propofol 8 hours after stopping dexmedetomidine ( p < 0.005). Dexmedetomidine dosage was 0.7 ± 0.2 μg/kg/hr. Before and after dexmedetomidine infusion, sedative doses remained unchanged (propofol 2.6 ± 1.2 vs 2.6 ± 1.2 mg/kg/hr; p = 0.23 and remifentanil 1.27 ± 0.17 vs 1.27 ± 0.16 μg/kg/hr; p = 0.52, respectively). Richmond Agitation-Sedation Scale was –4 (–4 to –3) before, –4 (–4 to –3) during, and –4 (–4 to –4) after dexmedetomidine ( p = 0.07). Conclusions: For a comparable level of sedation, switching from propofol to dexmedetomidine resulted in a reduction of catecholamine requirements in septic shock patients. Abstract : Supplemental Digital Content is available in the text.